Fine motor performance of children with ataxic cerebral palsy during tracing activity: A case report - Machado, Maraísa Fonseca [UNESP]; Araújo, Rita de Cássia Tibério [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (My University, 2014)
The aim of this study was to test the effect of weight bracelet and adapted pen on fine motor graphic activity performance. Two patients with a diagnosis of ataxic cerebral palsy from the Occupational Therapy service participated in the study. The effect of these adaptations was tested during tracing activities on a tablet, with records related to time, jerk, pressure and strokes. The data represent four experimental situations: a) without adaptation, b) with weight bracelet, c) with weight bracelet and weight on an adapted pen, and d) with weight on an adapted pen. Participant P1 showed less tremor and execution time in situation d, and less stroke and pressure in situation c. Participant P2 had a shorter execution time, tremor and pen force in situation d, and less stroke incidence in situation c. This study suggests that the prescription of weight using weight bracelet in addition to weight on an adapted a pen to cerebral palsy patients would be suitable to perform graphic tasks with higher quality.
Keywords: Cerebral palsy; Motor learning; Motor performance